Effectiveness Treatment of perineal wounds with compresses soaked in Betadine - Purnamasari, Feby; Nurhidayah, Nurhidayah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
The postpartum infection could have come from a wound infection experienced by the perineum. It is caused by wound incisions experienced infections and a tear of the birth canal or tear of the perineum. Perineal care is an effort to provide comfort for women who have given birth to avoid infection. The purpose of this research is to investigate the effectiveness of the use of betadine compress not given betadine on healing wounds in the perineum. The kind of research is quantitative using experimental design spring. Samples are to be taken as many as 30 people that is 15 people to the control group and 15 people to the case. This study was conducted from September -November 2022. The research results show there is no difference between the healing of wounds in the perineum control compress betadine with clusters of cases that do not compress betadine (the test Mann Whitney U p-value = 0,129 > 0,05) so that it can be concluded that both compress and non compress betadine and it is the same with betadine have a chance to heal in good